The power of calmness in times of the COVID-19 pandemic: The different roles of peace of mind and career calling in enhancing work engagement—A mediation analysis based on social support - Xi, Yiheng; Zhou, Li; Guo, Dong (Frontiers in Psychology, 2023)
The prevention and control of the COVID-19 pandemic has taken on a “New Normal” form, which necessitats a calm and peaceful social mentality. This study delves into the Chinese socioculturally oriented emotion construct of peace of mind (PoM) with regard to how it may affect employees’ work engagement in times of the pandemic. Based on the conversation of resource (COR) theory, we develop a model in which the relationship between PoM (i.e., a low-arousal positive affective state) and work engagement and the relationship between career calling (i.e., a high-arousal positive state) and work engagement are both mediated by social support. A battery of questionnaires was administered in 292 employees in 18 Chinese enterprises during the pandemic. The results show that both relationships were mediated by social support; furthermore, after the mediating effect of social support on the relationship between PoM and work engagement was controlled for, the relationship between career calling and social support failed to reach significance. The findings thus attest to the unique advantages of PoM in advancing employees’ resource conservation and in boosting interpersonal communication in a public crisis. Possible implications on applying the incentive mechanism of PoM in the workplace are discussed.